How do transnational networks facilitate the movement of Congolese migrants and refugees into Johannesburg? - Losango-Nzinga, Jean Didier (My University, 2008)
ABSTRACT. The failure of the 1990 political transition in the Democratic Republic of Congo to deliver on promises of better living conditions for all Congolese and the diminishing job opportunities available to young Congolese have resulted in many looking for economic opportunities outside their country of nationality. With most of the European and North American countries effectively off limits due to restrictive measures on migration (Bauman, 1998; Soguk 1999). The post-apartheid South Africa is relatively prosperous. This fact couple with a corrupt immigration and asylum system make the country very attractive for an increasing number of Congolese migrants who desire a better standard of living. Although the borders are relatively porous, the expense and hazards of moving require resources that are not available to all. This project explores how migrant networks can provide those resources through information and access to documentation, housing, and opportunities for income-generation. In particular, this thesis explores the role of social networks in structuring the movements of Congolese into Johannesburg and their integration into its social fabric. It intersects with a part of a growing body of literature demonstrating numerous new ways in which contemporary global migrants remain closely connected to their places of origin, to co-nationals or co-ethnics across nation-state borders, and indeed across the world 1(Transnational Communities Programme; 1999). While this analytical perspective has been applied fairly extensively to other groups of migrants, few scholars have sought to examine the extent to which refugees and asylum seekers maintain such a worldwide web of relationships (Crisp, 1999). Indeed, academic discourses on refugees, and also the practical efforts made on their behalf by United Nations High Commissioner of Refugees (UNHCR) and other humanitarian organizations, continue to be informed by the assumption of a rigid separation between the exile country of origin and country of asylum (Crisp, 1999). 1 Programme of a workshop on ‘Policy challenge of the new migrants diasporas’, Chatham House, London, 22-23 April 1999. Quoted by Jeff Crisp in: Policy challenges of the new diasporas: migrant networks and their impact on asylum flows and regimes. WPTC-99-05 Policy Research Unit, UNHCR, CP 2500, CH-1211 Geneva Switzerland. www.transcomm.ox.ac.uk/working%20papers/riia3.pdf Jean Didier Losango Nzinga 5 Against this background, social networks play an important role in facilitating migration, whether across borders or across regions (Guzman, Haslag and Orrenius 2004). These networks are likely to act as an important source of information to prospective migrants, refugees and asylum seekers, providing them with details on matters such as transport arrangements, entry requirements, asylum procedures and social welfare benefits, as well as the detention and deportation policies of different destination states (Crisp, 1999). Consequently, refugees and other migrants who have access to such data are better placed to negotiate entry into developed countries than those who do not2. 2 Given the increasingly important role these networks play in facilitating movement of people around the world today, the emergence of the internet plays a major role in making these networks possible. See report prepared for the Knowledge for Development Program of the World Bank: Role of Diaspora in Facilitating Participation in Global Knowledge Networks: Lessons of Red Caldas in Colombia (Bogota, December 2004).
Keywords: transnational networks